Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.1016/j.coviro.2017.04.005
|View full text |Cite
|
Sign up to set email alerts
|

Inactivated influenza virus vaccines: the future of TIV and QIV

Abstract: Influenza viruses continue to be a major public health concern, despite the availability of vaccines. Currently licensed influenza vaccines aim at the induction of antibodies that target hemagglutinin, the major antigenic determinant on the surface of influenza virions that is responsible for attachment of the virus to the host cell that is to be infected. Currently licensed influenza vaccines come as inactivated or live attenuated influenza vaccines and are tri- or quadrivalent as they contain antigens of two… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 48 publications
1
20
0
Order By: Relevance
“…In the absence of preexisting memory cells against H5 head epitopes, these cells overcome the often-observed dominance of HA head-specific B cells ( 21 , 22 ). The increase of H1 stalk-reactive antibodies in the TIV vaccination group was low (1.3-fold GMI; 95% CI, 1.1 to 1.5), which is consistent with an antibody response that preferentially targets the HA head domain ( 23 ).…”
Section: Resultssupporting
confidence: 61%
“…In the absence of preexisting memory cells against H5 head epitopes, these cells overcome the often-observed dominance of HA head-specific B cells ( 21 , 22 ). The increase of H1 stalk-reactive antibodies in the TIV vaccination group was low (1.3-fold GMI; 95% CI, 1.1 to 1.5), which is consistent with an antibody response that preferentially targets the HA head domain ( 23 ).…”
Section: Resultssupporting
confidence: 61%
“…Traditionally, the spread of IAV has been prevented by two vaccination strategies: inactivated influenza vaccine (IIV) and live-attenuated influenza vaccine (LAIV). Both IIV and LAIV primarily provide systemic immunity by inducing IAV-specific antibody responses (3,4). However, it is less clear if these vaccination strategies generate robust de novo IAV-specific CD4 or CD8 T cell responses within the lower lung mucosa (4)(5)(6)(7).…”
Section: Introductionmentioning
confidence: 99%
“…Seasonal influenza infections are prevented and controlled through annual vaccination campaigns to decrease IAV infections and viral transmission as well as to reduce their negative impact in the global economy. However, although vaccination remains the most effective approach to protect the population from seasonal infections, the effectiveness of current vaccination approaches is suboptimal [16,[31][32][33][39][40][41][42][43][44]. Thus, the production of improved prophylactic approaches, including universal vaccines, are highly desired.…”
Section: Influenza Virus Importance In Human Healthmentioning
confidence: 99%
“…Notably, the efficacy of vaccines against IAV infections can fluctuate and there is a significant immune response variability across the population. Factors such as previous exposure to IAV infections or vaccines, age, and the closeness of the match between the vaccine and circulating strains are important to explain differences in vaccine effectiveness between seasons and group populations [44,46,[150][151][152]. However, multiple reports have demonstrated that the host genetic background and polymorphisms on key immune response genes modulate the immune response to infection or vaccination [153][154][155][156][157][158][159][160].…”
Section: Snps In Genes That Influence the Iav Vaccine Responsementioning
confidence: 99%